Comparison of The Accuracy of CBCT and MDCT Imaging Modalities in Determining the Distance Between the Incus and the Facial Nerve and the Round Window and the Oval Window: A Cadaveric Cross-Sectional Study - Sharifishoshtari, Sanaz; Saki , Nader; Roozbahani, Zohreh; Mehrab, Yasamin; Hesari, Ali (Galen Medical Journal, 2025)
Background: Hearing loss is the most common birth defect, and cochlear implants are an effective treatment for severe sensorineural loss. This study compared CBCT and MDCT accuracy in measuring key ear structures to aid cochlear implant planning. Materials and Methods: In this cadaveric cross-sectional laboratory study, 12 temporal bones along with their covering soft tissue in the archive of the ENT department of Imam Khomeini Hospital in Ahvaz were studied. Imaging was performed using high-resolution CBCT, low-resolution CBCT, and MDCT modalities. Measurements were performed by an oral and maxillofacial radiologist and a general radiologist. The obtained data were analyzed descriptively and analytically in SPSS-21 software. Results: The results revealed a high agreement between the data related to the distance of the incus from the facial nerve and the distance of the oval window from the round window in High-resolution CBCT, Low-resolution CBCT, and MDCT images. However, there was a significant difference in the measurement of MDCT and low-resolution CBCT compared to high-resolution CBCT. There was no significant difference in the measurement between MDCT and low-resolution CBCT. Conclusion: Based on our study and some previous studies on quantitative measurements of CBCT and MDCT imaging, low-resolution CBCT can be more reliably replaced by MDCT and achieve acceptable results compared to MDCT using a lower radiation dose. More studies are needed regarding the significant difference between high-resolution CBCT and MDCT, but the higher resolution of the borders in high-resolution CBCT images may be the reason for this result.